(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Shakespeare’s main goal is to represent the women in their plays. The writers use the female characters of their plays of their representation. Feminist analysis seem to be the most quickly developing and widely-used approach to Shakespeare in recent times. Feminist critique deeply focuses on marriage traditions of courtesy, sex family structures. The study found that Shakespeare uses the gender style to represent female characters in her plays.